1983
DOI: 10.1080/05698198308981490
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Material Removal During Erosion of a Stainless Steel

Abstract: Solid particle erosion of an austenitic stainless steel was studied utilizing various metallographic techniques. Examination of single impacts on a polished surface resulted in a semiquantitative crater clmsiJication. It was, however, found that material removal generally involves the interactive effect of several cumulative impacts. Consequently, topography and internal structure of the target surface layer afier multiple impacts were investigated. In particular, preeroded targets were reexamined after additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…For a particular impact angle, normalized erosion rate increased with particle speed. This observation is in agreement with Söderberg et al [36] and Hutching et al [37] who observed greater material removal from the target specimen surface at higher particle speed and ascribed that to the high kinetic energy associated with the high speed particles. Figure 5b illustrates normalized erosion rate vs. impact angle for various particle speeds.…”
Section: Resultssupporting
confidence: 92%
“…For a particular impact angle, normalized erosion rate increased with particle speed. This observation is in agreement with Söderberg et al [36] and Hutching et al [37] who observed greater material removal from the target specimen surface at higher particle speed and ascribed that to the high kinetic energy associated with the high speed particles. Figure 5b illustrates normalized erosion rate vs. impact angle for various particle speeds.…”
Section: Resultssupporting
confidence: 92%
“…All of the alloy materials were austenof the eroded surface. [12,13,14] This is particularly surprising, itic, solid solution-strengthened alloys and provided a broad since the size of the plastically deformed region may reprevariation in mechanical properties. The Stellite-6 alloy consent a measure of energy absorbed before fracture during tained approximately 20 vol pct of hard carbides in a ductile erosion; only one erosion model [14] accounted for the plasticaustenitic matrix.…”
Section: Introductionmentioning
confidence: 94%
“…The influence of all the parameters is analyzed by the loss of material calculated by taking the weight loss using and accurate weighing machine. The Increase in the loss of material at higher particle speeds are due to that the abrasive particles is achieving greater kinetic energy [7,8]. As the angle of impact is increasing the rate of erosion reduces this due to the increase in the contact area.…”
Section: Solid Particle Erosion Of Duplex Stainless Steel With and Wimentioning
confidence: 99%